Kesehatan Jasmani Dalam Al-Qur'an (Studi Tematik Ayat-Ayat Syifa' Dalam Al-Qur'an) - Mahfudzah, Rika (ojs.unsiq.ac.id, 2022)
The Qur'an mentions various kinds of liver diseases that afflict humans, besides that it has also taught humans to continue to preserve the environment and maintain a clean place to live so that it does not become a nest of germs and bacteria. The Qur'an also urges to stay away from food and drink that contains disease and it also tells us how to treat ourselves when we are sick. Considering that the Qur'an helps humans in this area, the Qur'an calls itself a